Analysis Of The Current Situation Of The Provision Of Remote Services In Commercial Banks - Kamalova Jamila (Zien Journals, 2023)
In the world, attention is paid to the further increase of competition in the provision of highquality remote banking services to the population, to the assessment of the international ranking of the efficiency of commercial banks. In the fundamental reforms carried out in the banking and financial system in Uzbekistan, attention is paid to the development of commercial banks, increasing the confidence of business entities and the population in the banking system
Keywords: Commercial banks; payment system; remote banking services